Monitoring the acoustic activity of an aquatic insect population in relation to temperature, vegetation and noise. (29th August 2018) - Desjonquères, Camille; Rybak, Fanny; Ulloa, Juan Sebastian; Kempf, Alexandre; Bar Hen, Avner; Sueur, Jérôme
Abstract: Acoustic population monitoring is a noninvasive method that can be deployed continuously over long periods of time and at large spatial scales. One of the newly discovered threats acting on biological diversity is anthropogenic noise. High levels of anthropogenic noise occur in aquatic environments, yet their effects on animals living in freshwater habitats have very rarely been investigated. Here, we used acoustic monitoring and automatic detection to assess the acoustic activity of a population of a soniferous freshwater insect. The sounds emitted by the corixid Micronecta scholtzi were recorded in a Mediterranean pond with an array of 12 hydrophones. An automatic analysis based on a measure of the amplitude found in the frequency band of M. scholtzi was developed to assess the level of acoustic activity. We used functional linear models, accounting for the periodicity of the calling behaviour, to estimate the possible effect of temperature, vegetation and a noise due to an immersed engine. The automatic analysis was validated as an efficient method to measure the acoustic activity. The monitoring revealed a clear 24‐hr pattern in the acoustic activity of M. scholtzi and three peaks of activity during the morning. Functional linear models revealed negative effects of both temperature and vegetation and showed that an engine noise, played back for 2 hr during the night, elicited an increase in the level of acoustic activity of the population. Moreover, a cross‐correlation procedure showed that noise delayed the acoustic activity of the population. Our results suggest that acoustic survey and automatic detection are efficient methods to monitor the acoustic activity of an insect population especially in response to an anthropogenic disturbance.